Electronic commerce / Schneider, Gary P. (Australia : Thomson Learning Inc., 2007)
"This book provides comprehensive coverage and understanding of the social, cultural, organizational, and cognitive impacts of e-commerce technologies and advances on organizations around the world"--Provided by publisher.
Keywords: Electronic commerce